KHARISMA-MISTIK VERSUS RASIONAL-TEKNOKRATIK DALAM TRANSISI KEPEMIMPINAN INDONESIA. - Muizzuddin, Muizzuddin (Jurnal Bestari, 2001)
The President of Republic of Indonesia has changed four times, and now in the modern era. In the process of governing. The president has a spesific approach based on their background of educational, and cultural?include of mystical or believeness. In the fact, however, the mystical orientation is still colour their personality, especially for the the President that coming from java cultural, nemaly Soekarno, Soeharto and Abdurahman Wahid. The charisma, mystical, and the rational backgroud?include of education?become important reason to understant their style of how to manage the government.